Institute of Complicity in Extremist Crimes - Voronin, Vyacheslav N. (Sibirskoe ûridičeskoe obozrenie (Online), 2016)
This article analyzes the individual crimes of extremist orientation, located in Section 29 of the Criminal Code, which, in our opinion, is necessary in order to distinguish it from provisions of the General Part of the criminal law of complicity in a crime (Art. 282.1, 282.2 and 282.3 of the Criminal Code). The Author tries to reveal the reasons of legislative and lawapplication problems of crime elements by comparing them with the institute of complicity. As a result of the research the Author offers solutions to the problems identified.